Decreasing Posterior Femoral Condyle Offset Improves Intraoperative Correction of Flexion Contracture in Total Knee Arthroplasty - Leie, Murilo Anderson; Klasan, Antonio; Yeo, Wei Wang; Misso, Dylan; Coolican, Myles (The Journal of Knee Surgery, 2020)
Multiple intraoperative strategies are described to achieve full extension in total knee arthroplasty, but only a few studies have assessed the effect of the flexion gap on intraoperative improvement in flexion contracture. The aim of this study was to determine whether posterior condylar offset, in isolation, independently affects extension at the time of total knee arthroplasty.Two hundred and seventy-eight patients who underwent total knee arthroplasty for knee osteoarthritis and flexion contracture ≥ 5 degrees between January 2008 and July 2018 were included in this study. Patients with other factors that could affect knee extension at the time of surgery were excluded. We recorded the thickness of posterior femoral condyle bone resected as well as the thickness of the posterior femoral component chosen for each patient. Patients' knee extension was recorded under anesthetic, prior to resection and intraoperatively after total knee replacement.Average thickness of bone resection for the posteromedial femur was 12.64  ± 1.65 mm and for the posterolateral femur was 10.38  ± 1.52 mm. Using a linear regression model, we found that changes in posterior offset and implant downsizing influenced correction of fixed flexion deformity at the time of surgery. When patients had a combined posteromedial and posterolateral offset 2 mm thinner than the thickness of bone resected, there was an average correction of 3.5 degrees of flexion contracture.Our study demonstrated that posterior femoral condyle offset is an independent variable affecting correction of flexion contracture at the time of surgery in a gap balanced cruciate-retaining total knee arthroplasty. This is a level IV evidence study.
Keywords: total knee arthroplasty; extension gap; flexion gap; flexion contracture; posterior femoral offset